2018
DOI: 10.1080/23800127.2018.1494347
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing cycling experience in urban design research: a systematic literature review

Abstract: By conceptualizing a link between the cycling experience and the associated methods in understanding the former, the perspective of a cyclist is highlighted as an opportunity for research in urban design. A systematic review of 20 empirical papers across a variety of disciplines covering both walking and cycling experiences was conducted. This paper links social, sensory and spatial experiences, and connects these experiences to textual, visual and evaluative methodologies. This paper proposes how cycling can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
0
15
0
3
Order By: Relevance
“…Nevertheless, the interviews also suggested that the intrinsic qualities and enjoyment of cycling might potentially play a more important role in the choice to start travelling by bike-train than captured in our survey: the fact that the intrinsic qualities of cycling are often hard to put into words (and measure in a survey) should not lead us to underestimate their importance (Krizek 2018;Liu, Krishnamurthy and van Wesemael 2018;te Brömmelstroet et al 2019). Indeed, cycling is one of the transport modes which scores highest in terms of its positive affective qualities, with cyclists being among the happiest commuters (Wild and Woodward 2019).…”
Section: Triggers Of Bike-train Uptakementioning
confidence: 89%
“…Nevertheless, the interviews also suggested that the intrinsic qualities and enjoyment of cycling might potentially play a more important role in the choice to start travelling by bike-train than captured in our survey: the fact that the intrinsic qualities of cycling are often hard to put into words (and measure in a survey) should not lead us to underestimate their importance (Krizek 2018;Liu, Krishnamurthy and van Wesemael 2018;te Brömmelstroet et al 2019). Indeed, cycling is one of the transport modes which scores highest in terms of its positive affective qualities, with cyclists being among the happiest commuters (Wild and Woodward 2019).…”
Section: Triggers Of Bike-train Uptakementioning
confidence: 89%
“…Sallis et al (2004) already proposed greater interdisciplinary collaboration to prevent representations of cycling either as a form of physical activity, or as a mode of transport, or as a marker of cultural identity of discrete population groups. In this journal, Te Brömmelstroet et al (2017) call for planning practitioners to view cycling mobility more broadly to appreciate experiential features of citizenship and belonging alongside typical focus on cost and utility functions (also Liu, Krishnamurthy, and van Wesemael 2018). Influenced somewhat by recent qualitative studies, notably those based on lived experiences, and the identification of psycho-social factors affecting bicycle use (Pooley et al 2013;Pucher, Dill, and Handy 2010), we propose further interdisciplinary dialogue on age-related cycling normalisation.…”
Section: Introductionmentioning
confidence: 94%
“…These modalities also vary according to the two-wheeler used (e-bike, touring bike, mountain bike, etc.). Until recently, there has been relatively little research on touring cultures and the embodied experiences of cycling tourists (Liu et al, 2018; Spinney, 2006). A characteristic feature of independent cycling tourism is that cyclists use their own bicycles and other gear for (or when) transiting to the destination and moving through the destination.…”
Section: On Your Bikementioning
confidence: 99%